Cellulose/cysteine based thiol-ene UV cured adsorbent: removal of silver (I) ions from aqueous solution - BİRTANE, HATİCE; KAHRAMAN, MEMET VEZİR; AYDIN URUCU, OYA (SPRINGER, 2021)
In the present study, a novel, eco-friendly, and simple polymeric adsorbent was obtained from cellulose acetate butyrate (CAB) and cysteine (Cys) to remove silver (I) ions in the presence of a thiol-ene click reaction under UV rays. Accordingly, firstly, CAB was modified with acrylate groups to turn it into a photocurable resin. Then, the acrylate modified CAB obtained with the monomer having cysteine and triacrylate group was crosslinked by thiol-ene click reaction under UV rays to obtain an eco-friendly adsorbent. The adsorbent acquired -S-, -COO and -NH2 groups as a result of this reaction and these functional groups are known to have the ability to selectively couple with Ag(I) ions. The adsorbent was evaluated for the selective removal of Ag(I) ions from aqueous samples characterized by SEM, SEM-EDAX, and FTIR. To determine the most suitable conditions, the effect of important parameters such as pH and contact time was investigated. It was determined that the most suitable isotherm for adsorption was the Langmuir isotherm (R: 0.999). The efficacy of our eco-friendly adsorbent was investigated in a real stream and lake waters and very good results were achieved. [GRAPHICS] .
Keywords: Environmental samples; Silver; Eco-friendly adsorbent; Thiol-ene photocurable adsorbent; L-cysteine; SOLID-PHASE EXTRACTION; ENVIRONMENTAL-SAMPLES; AG I; ADSORPTION; PRECONCENTRATION; NANOCOMPOSITE; MERCURY(II); POLYMER; NICKEL; GOLD